The Influence of Inquiry Methods and Motor Educability on Dribbling Skills in Soccer - Alexon Alexon; Bayu Insanistyo; Binar Dewa Al Rajjab; Novriansyah Novriansyah (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
Research aims toaknow the influenceaMethod of Inquiry and Motor Educability Exerciseaagainst skillsaDribbling in FootballaBengkulu Young Shoots. Research conductsaresearch Experiment withaFactorial design. Sample insideaThis study included 48 athletesaTunas Muda KotaaBengkulu. Data analysis techniqueausing the t-test. The results of the research in this study are: 1. The results of the dribbling skills in soccer for SSB students who are taught using a modelainquiry exerciseaguided moreahigh in comparisonawith students who followainquiry learningafree. 2. Resultsadribbling skills of students have motoraeducability higheraheight than the childawho has a motoraeducabilitylow. 3. Several schoolsahave a workout scheduleaconcurrently between football extracurriculars, so thatadirectly inaimplementation of the exercise sometimes has toado the treetment and testanot simultaneously. This matterabe one of the obstacles in providing treatmentain the form of a training methodato students. 4. Studentsanot quarantined soaresearchers cannot control activityawhateverastudents doaout of scheduleaexercise is a nutritional problemastudents. Notastraightforward this thingacan affectaresearch. 5. Lack of comfortaand the serenity students getaat the time of doing the guided inquiry method and lackathe facility used by researchers to support the provisionathe training method when doing the methodathe free inquiry exercise.